Capacidades estatais municipais: o caso de Colatina(ES) frente ao desastre da barragem da Samarco (Fundão/MG) - Martins, Lorena Pinheiro (2023)
The paper analyzes the capacities of the municipal government to deal with public supply crises arising from water crisis situations, and how these local government capacities prepare or not the municipalities to deal with sudden situations, as occurred in the case of Fundão-MG disaster. Based on the literature on State Capacities and Multilevel Institutional Arrangements, this dissertation aims to understand how the municipality of Colatina-ES had state capacities to deal with the environmental and water problems caused and what were the responses of the institutions linked to environmental and water management in the municipality given the emerging problems. Methodologically, the theme is approached as a case study, focusing on state capacities and their pre- and post-disaster reconfigurations. In the context of the crisis caused by the Doce river water capture impediment and the complex situations that ensued, the case study contributes to the understanding of the multidimensional characteristics (environmental, social, economic, institutional) that constituted the scenario where institutional managers needed to negotiate alternatives with several social and political actors present in the researched municipality. From this theoretical-analytical framework and understanding of the few existing connections between the institutional matrix of SISNAMA and SINGREH, it was possible to highlight the existence of gaps that generate interpretive ambiguities on the part of managers. Regarding the institutional and political-relational capacities existing in the Colatina-ES city hall, as well as the challenges faced in the crisis situation, the research findings demonstrate that recent institutional capacities had been built, which provided reasonable support in the acute phase of the crisis. In fact, from the Crisis Cabinet established to deal with the chaos and public calamity situation, it was possible to establish articulations with various federal and state government agencies, as well as with the municipality of Governador Valadares, which was undergoing a similar situation at that time.